The effect of labor cost on innovation - Nain, Amrita; Wang, Yan; Michael Lee-Chin & Family Institute for Strategic Business Studies (My University, 2019)
Using minimum wage changes as an exogenous shock to the cost of low-skill labor, we show that corporate innovative output declines after the shock, especially in industries dependent on unskilled labor. The substitutability between technology and unskilled labor plays a key role in the response of innovative output to minimum wage shocks. We identify technology that reduces the demand for unskilled labor either through automation or due to capital-skill complementarity. We find that minimum wage shocks have a less deleterious impact on the innovative output of firms developing technology that reduces the demand for unskilled labor. Valuation Insight: Higher minimum wages are found to decrease patents and patent citations, esp. in industries with more low-skill workers. In these industries the incentive to develop new technology that requires production workers decreases with higher minimum wages. Thus innovative activity decreases. Value creation is affected more negatively when minimum wages increase in firms that employ more low-wage workers and firms that focus their innovation on technology that requires labor rather than replaces it.
49 p. ; Includes bibliographical references (pp. 30-32). ; "October 2019";